Prevalence and Associated Factors of Depression among Perimenopausal Women of Tokha Municipality, Kathmandu - Piya, Sriyansu; Pradhan, Bijay Lal; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Depression is common among all population but even more in women going through menopause. It is due to hormonal changes during that period paired with certain behavioral as well as biological factors and even certain life events that can have devastating effects on the person. The objective of this research is to find the prevalence and associated factor of perimenopausal depression along with factors associated with it. Methods A Cross sectional descriptive study was conducted in Ward no. 10 and 11 of Tokha Municipality among 205 perimenopausal women. Permission was taken from Research department of National Open College also from the ward offices of Tokha Municipality, Kathmandu. The collected data was entered in Microsoft excel and analyzed in SPSS version 22. Results The prevalence of depression among perimenopausal women was more than one-third (39.2%), 28.7% of respondents having mild depression, 8.3% having moderate depression, 1.1% having moderately severe and 1.1% having severe depression. Depression was found to have significant association with loss of family members or peers and help seeking intention of the respondents. Conclusions The study identified prevalence of depression among perimenopausal women. Loss of closed ones and help seeking intentions were seen to be associated with depression during perimenopause.